Growth and metabolic change of the muskmelon fertilized with biofertilizer commercials - Silva, Juliana Leite da; Silva, Kecio Emanuel dos Santos; Rocha, Daniel Nunes Sodré; Barbosa, Thais Cristina da Silva; Oliveira, Zezia Verônica Silva Ramos; Mesquita, Alessandro Carlos (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
The region of the Submédio Vale do São Francisco he management of conventional fertilization in the cultivation of melon is highlighted, however, the constant use of these fertilizers has promoted a search for alternative managements that seek to reduce environmental impacts and improving productivity. The use of biofertilizers has been an alternative for the production of many crops, including melon, as this product has the ability to supply some essential nutrients to plants. This study aims to evaluate the influence of different doses of two biofertilizers (Algamare® and Vorax®), on the growth and metabolism of melon (cv. Gold Mine) throughout its cycle. The experimental design used was in randomized blocks, in a 5x3 factorial scheme, comprising two types of biofertilizers (Algamare® and Vorax®), combined into five dosages: (dosages 1 - water (control); 2 - 288/40 µl; 3 - 576/80 µl; 4 - 1.152/160 µl; 5 - 2.304/320 µl) and three evaluation periods (30, 45 e 60 DAT), with three repetitions. The following growth variables were evaluated: plant height, stem diameter, leaf area, number of leaves. The biochemical variables analyzed were: chlorophyll content, activity of the enzyme nitrate reductase (leaf tissue), reducing sugars, total soluble sugars, total soluble proteins and proline. It was concluded that the use of the biofertilizer in the melon crop promoted an increase in the growth and metabolism of the plant, contributing to the increase in the number of leaves, the chlorophyll content, leaf area of the plant, activity of the enzyme nitrate reductase and the amino acid proline. It is recommended to combine the biofertilizers Algamare® and Vorax® in the dosage of 576/80 µl, respectively.